Novel and Efficient Access to Flavones under Mild Conditions: Aqueous HI‐Mediated Cascade Cyclization/Oxidative Radical Reaction of 2‐Propynolphenols. Issue 40 (15th October 2018) - Song, Xian‐Rong; Li, Ren; Yang, Tao; Chen, Xi; Ding, Haixin; Xiao, Qiang; Liang, Yong‐Min
Abstract : Herein we disclose a metal‐free and efficient method for the direct conversion of 2‐propynolphenols to biologically important flavones using aqueous HI as the promoter. This transformation was proved via 4‐iodo‐2 H ‐chromenes intermediate, which was simultaneously conversed to corresponding flavones by a Csp2 −I bond cleavage and a C–O bond formation under air. Abstract : Herein we disclose a metal‐free and efficient method for the direct conversion of 2‐propynolphenols to biologically important flavones using aqueous HI as the promoter. This transformation was proved via 4‐iodo‐2 H ‐chromenes intermediate, which was simultaneously conversed to corresponding flavones by a Csp2 –I bond cleavage and a C–O bond formation under air.